Trade integration in West Africa: Does the quality of institutions matter? - Vigninou Gammadigbe (Journal of African Trade, 2021)
When asked why the level of intra-regional trade in West Africa is low despite regional integration efforts, the literature highlights the poorly diversified structure of economies, the non-application of community arrangements, the inconsistency or mismanagement of trade policies, supply constraints, and inadequate transport infrastructure. Without calling into question the relevance of these factors, this paper investigates the contribution of institutional variables to the explanation of trade flows in West Africa over the period from 1996 to 2018. Using a gravity model, the study shows that institutional quality matters. The quality of institutions in the Economic Community of West African States (ECOWAS) countries influences bilateral trade. Political stability is an essential component of the quality of the institutions that determine trade in the ECOWAS zone. These results suggest that more than trade liberalization is needed to deepen trade integration and that institutional reforms and harmonization in West Africa are required.
Keywords: F15; O17; C23; 330; Institutions; trade; gravity model; panel data